Violence, emotion and place: The case of five murders involving sex workers - Wattis, Louise (Crime, media, culture, 2020)
This article examines a series of murders involving young women linked to sex work, which occurred in the same Northern town between 1998 and 2003. It explores the case on a number of levels. First, it situates violence, and these murders specifically, in the localised spaces of advanced marginality, which follow in the wake of deindustrialisation and economic decline. Second, the article links these murders to sex workers’ disproportionate vulnerability to violence as a result of social stigma and situational risk. However, informed by auto-ethnography and the growing recognition that there is potential for academic analysis within criminology to include the criminologist’s own emotional engagement, the discussion moves on to explore the author’s personal reflection on this series of murders derived from vicarious connection and proximity to victims. In addition, the author draws on the concepts of spectrality and haunting, which have gained currency across the social sciences, to illuminate the irrevocable connections between place, violence and emotion at the level of the local. The concept of spectrality offers a means of envisaging how the past continues to occupy and disrupt the present. Studies of place deploy spectrality and the figure of the ghost to consider how acts of violence and atrocity transform the essence of physical and social space. For the purposes of this article, the concept of haunting is used to explore these young women’s lives and deaths, which retain a strong presence in the collective memory due to their powerful connections to place, as well as the cultural work of the media in keeping them alive in the local imagination. Finally, the political potential of haunting - as a means to confront past and ongoing injustices, is also considered, which draws attention to the combined structural conditions in which these young women were murdered.